Environmental regulation and the upgrading of marine industries: evidence from China’s coastal provinces - Liu, Lu; Wang, Hongwei; Cai, Daxia (Frontiers in Marine Science, 2025)
IntroductionUpgrading China’s marine industrial structure toward sustainability and higher value is central to the nation’s strategy of becoming a maritime power. Environmental regulation plays a pivotal role in this transition, yet its influence in the marine sector remains insufficiently examined.MethodsUsing panel data from 11 coastal provinces, this study distinguishes between command-and-control and market-based regulation, and applies a threshold regression model to evaluate their respective impacts and interactions.ResultsThe analysis reveals that command-and-control regulation follows an inverted U-shaped pattern: moderate enforcement encourages industrial optimization, while overly stringent measures suppress innovation and slow transformation. Market-based regulation currently has a net negative effect, reflecting limited effectiveness under existing policy conditions. Nonetheless, evidence points to a potential U-shaped relationship, suggesting that better policy design and implementation could reverse this trend. Threshold results further show that while command-and-control regulation is unaffected by market-based intensity, strong command-and-control enforcement markedly weakens the impact of market-based tools.DiscussionThese findings underscore the need to calibrate regulatory intensity and improve coordination between regulatory instruments. A balanced mix of policies, tailored to the specific dynamics of the marine economy, can help unlock the full potential of environmental regulation and support high-quality, sustainable growth in China’s marine industries.